Gaussian cloud and TOPSIS based power supply quality evaluation method - Weitao Tan; Yuejun Ge; Bo Chen; Jiahan Ding; Xin Luo; Zhian Lin; Weiqiang Qiu; Zhenzhi Lin (Energy Reports, 2022)
The accurate evaluation of power supply quality in the distribution network is regarded as an important way to improve the power quality of the user side and guide the power quality management of the power grid. Thus, a comprehensive evaluation method of the power supply quality based on the Gaussian cloud (GC) and the technique for order preference by similarity to ideal solution (TOPSIS) is proposed in this work. First, multiple evaluation indexes of the power supply quality are customized based on the measurement data of the distribution network and the power supply work order. On this basis, an index conversion method based on Gaussian cloud is adopted to convert the above indexes into Gaussian cloud distribution. Then, a comprehensive evaluation method of power supply quality based on TOPSIS is proposed for converting the similarity between Gaussian clouds into comprehensive evaluation results. Case study on power supply quality in Zhejiang province, China is employed to demonstrate the effectiveness and rationality of the proposed method. The result shows that the power supply quality can be evaluated by proposed method in an objective and reasonable manner.